2005
DOI: 10.1128/iai.73.8.4539-4547.2005
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of gp91 Phagocytic Oxidase and Reactive Oxygen Species in Neutrophils by an AvirulentSalmonella entericaSerovar Infantis Strain Protects Gnotobiotic Piglets from Lethal Challenge with Serovar Typhimurium Strain F98 without Inducing Intestinal Pathology

Abstract: Preinoculation of susceptible 5-day-old gnotobiotic piglets with Salmonella enterica serovar Infantis strain 1326/28⌽ r stimulates neutrophil migration into the intestine, which rapidly protects the pigs against a subsequent (normally lethal) challenge with S. enterica serovar Typhimurium strain F98. Here we show that inoculation with either 1326/28⌽ r or F98 activated reactive oxygen species (ROS) in neutrophils via NADPH pathways in vivo and in vitro and that the survival of both Salmonella strains was incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…However, this response, at least in gnotobiotic pigs, can be absent after infection with attenuated mutants (Splichal et al., 2005; Trebichavsky et al., 2006). From the vaccine design point of view it is desirable that the potential vaccine strain induces the inflammatory response as under some circumstances the inflammation and neutrophil infiltration may protect pigs from the superinfection with the wild‐type strain (Dlabac et al., 1997; Foster et al., 2003, 2005; Splichal et al., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, this response, at least in gnotobiotic pigs, can be absent after infection with attenuated mutants (Splichal et al., 2005; Trebichavsky et al., 2006). From the vaccine design point of view it is desirable that the potential vaccine strain induces the inflammatory response as under some circumstances the inflammation and neutrophil infiltration may protect pigs from the superinfection with the wild‐type strain (Dlabac et al., 1997; Foster et al., 2003, 2005; Splichal et al., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to preventing colonization by the avirulent strain, studies in pigs have shown that this approach can induce a rapid form of protection against clinical diarrhea [ 40 ] not related to colonization inhibition. This latter protective effect appears to involve an influx of neutrophils and macrophages into the site of colonization in the intestinal mucosa and involves production of antibacterial ROS at the site of the acute infection [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…One reason for the high effectivity of EcN could be its rough chemotype LPS (R-LPS) [80]. GN minipigs colonized with R-LPS S. Typhimurium F98 or S. Typhimurium SF1591 were resistant to subsequent infection with virulent S. Infantis 1326/28 [81,82] or S. Typhimurium LT2 [83], respectively. S. Typhimurium LT2 is avirulent for one-week-old CV piglets [53], which are protected by complex microbiota mediating their colonization resistance [26,27].…”
Section: Discussionmentioning
confidence: 99%